Legal Aspects of Regional Government Strategies in Overcoming Unemployment, Problems and Solutions - Titik Budiyanti (Law Development Journal, 2020)
The problems discussed in this study are "the legal aspects of local government strategies in overcoming unemployment, problems and solutions in Demak Regency". In order to discuss this problem, the approach method used is a normative juridical approach, which examines the law that is conceptualized as a norm or rule that applies in society. Sources of data in this study are secondary data sources obtained from primary, secondary and tertiary legal materials.From the results of the research and discussion, it was concluded that: the legal aspects of the regional government strategy in tackling unemployment in Demak Regency by establishing policies of the Demak Regency Government in attracting investors/ investors, developing employment opportunities, implementing rural productive labor intensive, implementing labor placements, carry out job training and local government policies in collaboration with companies and non-governmental organizations. Meanwhile, the problems faced by the Regional Government in Tackling Unemployment in Demak Regency are (1) high unemployment. The solution is to implement an employment opportunity expansion program, the implementation of rural productive labor-intensive activities, training and placement of workers (AKL, AKAD / transmigration and AKAN);Keywords : Unemployment; Regional government; Policy; work training